Spray-Dried Inhalable Microparticles Combining Remdesivir and Ebselen against SARS-CoV-2 Infection - Tushar Saha; Shubhra Sinha; Rhodri Harfoot; Miguel E. Quiñones-Mateu; Shyamal C. Das (MDPI AG, 2023)
There is a continuous effort to develop efficient treatments for coronavirus disease 2019 (COVID-19) and other viral respiratory diseases. Among the different strategies, inhaled treatment is considered one of the most logical and efficient approaches to treating COVID-19, as the causative "SARS-CoV-2 virus RNA" predominantly infects the respiratory tract. COVID-19 treatments initially relied on repurposed drugs, with a few additional strategies developed during the last two years, and all of them are based on monotherapy. However, drug combinations have been found to be more effective than monotherapy in other viral diseases such as HIV, influenza, and hepatitis C virus. In the case of SARS-CoV-2 infection, in vitro studies have shown synergistic antiviral activity combining remdesivir with ebselen, an organoselenium compound. Therefore, these drug combinations could ensure better therapeutic outcomes than the individual agents. In this study, we developed a dry powder formulation containing remdesivir and ebselen using a spray-drying technique and used L-leucine as an aerosolization enhancer. The prepared dry powders were spherical and crystalline, with a mean particle size between 1 and 3 µm, indicating their suitability for inhalation. The emitted dose (ED) and fine particle fraction (FPF) of remdesivir- and ebselen-containing dry powders were ~80% and ~57% when prepared without L-leucine. The ED as well as the FPF significantly increased with values of >86% and >67%, respectively, when L-leucine was incorporated. More importantly, the single and combinational dry powder of remdesivir and ebselen showed minimal cytotoxicity (CC50 > 100 μM) in Calu-3 cells, retaining their anti-SARS-CoV-2 properties (EC50 2.77 to 18.64 μM). In summary, we developed an inhalable dry powder combination of remdesivir and ebselen using a spray-drying technique. The spray-dried inhalable microparticles retained their limited cytotoxicity and specific antiviral properties. Future in vivo studies are needed to verify the potential use of these remdesivir/ebselen combinational spray-dried inhalable microparticles to block the SARS-CoV-2 replication in the respiratory tract.